Posted by Maria on Tuesday, March 31, 2009 at 7:01pm.
x-sqrt(2x+1) = 7
x - 7 = sqrt(2x+1)
x^2 - 14x + 49 = 2x+1 ==>
x^2 - 16x + 48 = 0
split this up into:
(x - 12) * ( x - 4 ) = 0
so, x can technically be 12 or 4
12 - sqrt(24+1) does = 7
- Math - betty, Tuesday, March 31, 2009 at 7:09pm
x^2 times (2x+1 )
equals 2x^3 + 2x^2 -7 =0
- Math - betty, Tuesday, March 31, 2009 at 7:12pm
ohhh I'm so sorry. I misread the question...but your answer is still wrong
you would square both sides by 2
and then and up w/ 2x+1 = 49
- Math - Maria, Tuesday, March 31, 2009 at 7:15pm
What about the x?
- Math - Reiny, Tuesday, March 31, 2009 at 7:49pm
Maria, you are correct
x = 12 is the right answer, since x= 4 does not verify when you try it back in the original.
Answer this Question
More Related Questions
- Math Help please!! - Could someone show me how to solve these problems step by ...
- Math - So I am supposed to solve this without using a calculator: Sqrt/10 - ...
- Inequality - When I solve the inquality 2x^2 - 6 < 0, I get x < + or - ...
- Math(Roots) - sqrt(24) *I don't really get this stuff.Can somebody please help ...
- Math - find any stationary points of the function g(x) = (2x-3)square root of 5+...
- Math - How do you find a square root of a number that's not a perfect square? I'...
- MATH - I need to simply this equation, but I got stuck. h/(4-sqrt(16+h)) = y ...
- math,algebra,help - Directions are simplify by combining like terms. x radiacal ...
- Mathematics - sqrt 6 * sqrt 8 also sqrt 7 * sqrt 5 6.92820323 and 5.916079783 So...
- Calculus - Please look at my work below: Solve the initial-value problem. y'' + ...